Diets Enriched with Conventional or High-Oleic Acid Canola Oils Lower Atherogenic Lipids and Lipoproteins Compared to a Diet with a Western Fatty Acid Profile in Adults with Central Adiposity. Issue 3 (15th February 2019) - Bowen, Kate J; Kris-Etherton, Penny M; West, Sheila G; Fleming, Jennifer A; Connelly, Philip W; Lamarche, Benoît; Couture, Patrick; Jenkins, David J A; Taylor, Carla G; Zahradka, Peter; Hammad, Shatha S; Sihag, Jyoti; et al.
ABSTRACT: Background: Novel oils high in monounsaturated fatty acids (MUFAs) and low in saturated fatty acids (SFAs) are an alternative to partially hydrogenated oils high in trans -unsaturated fatty acids. There is widespread use of high-MUFA oils across the food industry; however, limited knowledge of their cardiovascular impact exists. Objectives: We investigated the effects of diets containing canola oil, high-oleic acid canola oil (HOCO), and a control oil blend (diet formulated to emulate a Western fat profile) on lipids, lipoproteins, and apolipoproteins (apos), as secondary outcomes of the trial. Methods: In a multi-center, double-blind, randomized, 3-period crossover, controlled feeding trial, men ( n  = 44) and women ( n  = 75) with a mean age of 44 y, mean body mass index (BMI; in kg/m 2 ) of 31.7, and an increased waist circumference plus ≥1 metabolic syndrome criteria consumed prepared, weight-maintenance diets containing canola oil [17.5% MUFAs, 9.2% polyunsaturated fatty acids (PUFAs), 6.6% SFAs], HOCO (19.1% MUFAs, 7.0% PUFAs, 6.4% SFAs), or control oil (10.5% MUFAs, 10.0% PUFAs, 12.3% SFAs) for 6 wk with ≥4-wk washouts. Fasting serum lipids were assessed at baseline and 6 wk. Diet effects were examined using a repeated measures mixed model. Results: Compared with the control, canola and HOCO diets resulted in lower endpoint total cholesterol (TC; −4.2% and −3.4%; P  < 0.0001), LDL cholesterol (−6.6% and −5.6%; P  < 0.0001), apoB (−3.7% and −3.4%; P  = 0.002), and non-HDL cholesterol (−4.5% and −4.0%; P  = 0.001), with no differences between canola diets. The TC:HDL cholesterol and apoB:apoA1 ratios were lower after the HOCO diet than after the control diet (−3.7% and −3.4%, respectively). There were no diet effects on triglyceride, HDL cholesterol, or apoA1 concentrations. Conclusions: HOCO, with increased MUFAs at the expense of decreased PUFAs, elicited beneficial effects on lipids and lipoproteins comparable to conventional canola oil and consistent with reduced cardiovascular disease risk in adults with central adiposity. This trial was registered at www.clinicaltrials.gov as NCT02029833.